II A-TOPAR ELEMENTLERIN OQÍTÍWDA KLASTER METODÍNAN PAYDALANÍW - Jumabaev, B.A.; Sh.Zaripbaev, K.; Aytbaeva, X.B. (SCIENCE and SOCIETY, 2024)
This article discusses the use of the Cluster method in teaching elements of group II A in chemistry lessons. In class activities, this method is considered as a set of ideas expressed by students and increases students' creativity and activity.